KEWENANGAN PENGELOLAAN HARTA KEKAYAAN ORANG DIBAWAH PENGAMPUAN OLEH BALAI HARTA PENINGGALAN SURABAYA - Wisuda, Selvia (Jurnal Magister Hukum Perspektif, 2023)
Balai Harta Warisan existed since the Dutch era to Indonesia around 1596. In order to find out the position of Balai Harta Warisan which has the task of managing the assets of people under supervision when it is related to positive law in Indonesia. With empirical juridical research, there will be primary and secondary data that will be processed. The results showed that the position of Balai Harta Peningalan is still recognized as a state institution and is still valid. The function of Balai Harta Pengrelican is to resolve issues of guardianship, custody, absence and inheritance that have no authority, etc. in accordance with article 3 of the Decree of the Minister of Justice and has the task of representing and taking care of the interests of people who cannot carry out their own interests. As a supervisor to protect the interests of Curandus and protect him from the actions of the custodians who may cause losses to his property while still within the time of custody. Carry out bookkeeping and registration of wills in accordance with the law and carry out the settlement of bankruptcy problems in accordance with the law. At present Balai Harta Warisan in Indonesia has a working area covering Balai Harta Warisan Jakarta, Surabaya, Semarang, Medan and Makassar Keywords: Relic Hall, Forgiveness, Wealth Property